(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The foundations of upbringing are laid in the family. It is a school of life that nurtures all human relationships and children that should be formed in a child. The necessary opportunities will be created for them to acquire a profession according to their interests, to have a perfect knowledge of the rules of ethics and to follow them.